MoireTrees: Visualization and Interaction for Multi-Hierarchical Data - Mahnas Jean Mohammadi-Aragh; T. J. Jankun-Kelly (EuroVis'05: Proceedings of the Joint Eurographics - IEEE VGTC Symposium on Visualization, 2005)
Visualizing hierarchical data is one of the core areas of information visualization. Most of these techniques focus on single hierarchies - hierarchies with a single root element and a single path to each element. In contrast, this work focuses on the browsing of multi-hierarchies - hierarchies with multiple roots or multiple paths per element. A radial focus+context display algorithm and interaction methods are introduced to explore such multi-hierarchical data. A series of examples demonstrate the effectiveness of our new visualization.